2006
DOI: 10.1037/0096-1523.32.2.226
|View full text |Cite
|
Sign up to set email alerts
|

On the surprising salience of curvature in grouping by proximity.

Abstract: The authors conducted 3 experiments to explore the roles of curvature, density, and relative proximity in the perceptual organization of ambiguous dot patterns. To this end, they developed a new family of regular dot patterns that tend to be perceptually grouped into parallel contours, dot-sampled structured grids (DSGs). DSGs are similar to the dot lattices used to study grouping by proximity, except that only one of the potential organizations is rectilinear; the others are curvilinear. The authors used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“…One possibility is that external features are quite useful for triggering the neural mechanisms responsible for the detection of perceptual input specifying the stimulus as a face (processing of "first-order relations" in Maurer et al, 2002). This idea is not so surprising, since facial contours have been found to be significant in the initial stages of development of face processing skills (Mondloch et al, 1999;Mondloch et al, 2002;Pascalis et al, 1995;Simion et al, 2001), and contours in general, have shown themselves to be crucial for shape perception in objects (Breitmeyer et al, 2006;De Winter and Wagemans, 2003;Lamote and Wagemans, 1999;Seghier and Vuilleumier, 2006;Strother and Kubovy, 2006).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One possibility is that external features are quite useful for triggering the neural mechanisms responsible for the detection of perceptual input specifying the stimulus as a face (processing of "first-order relations" in Maurer et al, 2002). This idea is not so surprising, since facial contours have been found to be significant in the initial stages of development of face processing skills (Mondloch et al, 1999;Mondloch et al, 2002;Pascalis et al, 1995;Simion et al, 2001), and contours in general, have shown themselves to be crucial for shape perception in objects (Breitmeyer et al, 2006;De Winter and Wagemans, 2003;Lamote and Wagemans, 1999;Seghier and Vuilleumier, 2006;Strother and Kubovy, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…External features may also be relevant when new face representations are being constructed (Sergent, 1986) and face processing skills are developing (Mondloch et al, 1999;Mondloch et al, 2002;Pascalis et al, 1995;Simion et al, 2001). The relevance of contours is revealed in several experiments on shape perception (Breitmeyer et al, 2006;De Winter and Wagemans, 2003;Lamote and Wagemans, 1999;Seghier and Vuilleumier, 2006;Strother and Kubovy, 2006) and supported by the existence of neurons in the visual cortex responding to them (Peterhans and von der Heydt, 1991).…”
Section: Introductionmentioning
confidence: 96%
“…This was found to be the case in rectilinear dot lattices (Kubovy & Wagemans, 1995). However, when different dot structures were investigated, it became clear that curvilinear grouping patterns (e.g., Figure 8A) could be stronger than rectilinear groupings (Strother & Kubovy, 2006) even with distance between elements was held constant. This suggests that proximity alone is not the only factor to govern grouping in these patterns.…”
Section: Non-accidentalness and Regularitymentioning
confidence: 95%
“…Although the space of all lattices could be categorised into six different classes depending on their symmetry properties, this global configuration aspect did not affect the grouping in these lattices, leaving distance as the only factor that affects proximity grouping. More recently though, it has been found that other factors, such as curvilinear structure, can also play a role in grouping by proximity (Strother & Kubovy, 2006).…”
Section: Proximity Quantitative Accountsmentioning
confidence: 99%
“…Strikingly, the same saliency measure works also for the classical piecewise constant textures, and therefore it fully generalizes existing theories based on feature gradients. The same measure may also explain recent findings about an unexpected salience of curvature in grouping by proximity in dot-sampled structured grids (20). Furthermore, smoothly varying ODTs also have been used in studies of sensitivity to orientation modulations (e.g., refs.…”
Section: Discussionmentioning
confidence: 57%